Membrane bound modified form of clade B Env, JRCSF is suitable for immunogen design as it is efficiently cleaved and displays all the broadly neutralizing epitopes including V2 and C2 domain-dependent conformational epitopes. Issue 1 (December 2016) - Das, Supratik; Boliar, Saikat; Mitra, Nivedita; Samal, Sweety; Bansal, Manish; Koff, Wayne; Chakrabarti, Bimal
Abstract Background Antigenicity of HIV-1 envelope proteins (Envs) of both lab-adapted and primary isolates expressed on the cell surface rarely match with in vitro neutralization of viruses, pseudo-typed with corresponding Envs. Often, both neutralizing and non-neutralizing antibodies bind to Envs expressed on the cell membrane. This could be due to the lack of efficient cleavage of Env expressed on the cell surface. Naturally occurring, efficiently cleaved Envs with appropriate antigenic properties are relatively rare. Given viral diversity it is essential to increase the pool of candidate Envs suitable for immunogen design. Previously, it has been reported that JRFL Env is the only clade B Env, which is efficiently cleaved on the cell surface and retains desirable antigenic properties. JRCSF is a clade B Env isolated from the same patient as JRFL. JRCSF Env has not been explored aggressively for designing immunogen as the binding characteristics of JRCSF Env to broadly neutralizing antibodies on the cell surface and its cleavage status are unknown. Results Although JRCSF preferentially binds to most of the other gp120-directed neutralizing antibodies and cleavage dependent antibody, PGT151 efficiently, it binds poorly to CD4-binding-site-directed (CD4-bs-directed) neutralizing antibodies on cell surface. Membrane bound form of modified JRCSF Env containing the N197D mutation binds to CD4-bs-directed neutralizing antibodies better than JRFL, without debilitating its ability to bind quaternary epitope-directed neutralizing antibodies or exposing the CD4i antibody epitopes. In comparison to JRFL (E168K), JRCSF Env binds more efficiently to PG9/PGT145 class of V1/V2-directed conformational antibodies. Biochemical, cell surface staining and gp120 shedding experiments suggest that JRCSF is efficiently cleaved on the cell surface. Conclusions Binding of JRCSF Env expressed on cell surface to the various HIV-1 Env-directed antibodies has not been reported earlier. Here, for the first time, we report that compared to JRFL, JRCSF displays epitopes for a larger number of broadly neutralizing antibodies and is also efficiently cleaved when expressed on the cell surface. Thus, considering the diversity of viral Envs and the discovery of conformation dependent glycan-directed antibodies in HIV-1 infected individuals, an innately cleaved JRCSF Env as present on the viral membrane and displaying those distinct epitopes may be an important candidate for immunogen design.